Effect of enalapril in children with steroid resistant primary nephrotic syndrome - L. P. Primi Atmikasari; M. P. Damanik; Tonny Sadjimin (Indonesian Pediatric Society, 2007)
Background A significant proportion of children with nephrotic syndrome become steroid dependent or steroid resistant who need further medication with cytostatic or other immunosuppressive drugs such as cyclophosphamide or chlorambucil. Unfortunately studies show that the drugs give no good results and cause adverse effects.Objective To establish the effect of enalapril in decreasing proteinuria in children with steroid resistant nephrotic syndrome.Methods We conducted a clinical trial in Nephrology Division, Pediatrics Department, Dr. Sardjito General Hospital from January 2004 to October 2005. Subjects were randomized to either receive prednisone and enalapril (Enalapril Group) or prednisone and cyclophosphamide (CPA Group). The main parameter was proteinuria level, which was examined at the beginning of the study and then every two weeks for eight weeks.Results Remission rate in enalapril group was 96% whereas in CPA group was 82% (P=0.09). Proteinuria level reduction in Enalapril Group from the beginning until the end was 606.92 mg/dl (99%) whereas in CPA Group the reduction was 712.97 mg/dl (91%). Statistically, there was no significant difference in the average decrease of proteinuria level between both groups (P=0.30). Odds ratio for overall adverse events in combined prednisone and enalapril therapy group compared to combined prednisone and cyclophosphamide therapy group was 0.29 (CI 95% 0.17;0.41).Conclusion Combined prednisone and enalapril has similar effect tocombined prednisone and cyclophosphamide in children with steroidresistant nephrotic syndrome. Overall adverse events in combinedprednisone and enalapril group was lower than that in combinedprednisone and cyclophosphamide group.